Report of the Core Group on Open Education - Planning Commission (Planning Commission Government of India, 1992)
The Report of the Core Group on Open Education outlines strategies for expanding flexible and accessible education in India during the Eighth Plan (1992–1997). The document emphasizes the evolution from correspondence education to open learning systems (OLS), which provide open admission, diverse subject choices, adaptable instructional designs, and vocational training opportunities. Initiatives like Open Universities, National Open School, Community Polytechnics, TRYSEM, Vidnyan Ashram, and Shramik Vidyapeeths illustrate the integration of education with socio-economic development, particularly in rural areas. Key goals include universal elementary education, employment generation, and skill enhancement for underprivileged populations. The report advocates collaborative funding, community involvement, and strategic planning to ensure sustainable, inclusive, and market-relevant educational opportunities across India.
Planning Commission Government of India New Delhi (February 1992)
Keywords: Open Education; Distance Learning; Vocational Training; Rural Employment; Community Polytechnics; National Open School; Lifelong Education; Skill Development; Educational Access; Non-Conventional Education; TRYSEM Program; Manpower Development